2020
DOI: 10.1158/2326-6066.cir-19-0394
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CMTM6 Suppresses Stem Cell–Like Properties and Enhances Antitumor Immunity in Head and Neck Squamous Cell Carcinoma

Abstract: CMTM6, a regulator of PD-L1 expression, also modulates tumor immunity. Little is known about the function of CMTM6 and its mechanism of action in head and neck squamous cell carcinoma (HNSCC). In this study, we found by IHC analysis that CMTM6 overexpression predicted a poor prognosis for patients with HNSCC. We discovered that CMTM6 expression was correlated with increased activity through the Wnt/β-catenin signaling pathway, which is essential for tumorigenesis, maintenance of cancer stem cells (CSC), and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 50 publications
4
110
3
Order By: Relevance
“…Elevated expression of CMTM6 was frequently accompanied with worse malignant phenomenon, such as with high AFP level, large tumor size, advanced TNM stage, vascular invasion in a large cohort of 619 HCC cases (In Zhu's study, only 75 HCC samples were collected). Our data was in line with other studies indicating that increased CMTM6 expression was presented in gliomaand Head and Neck Squamous Cell Carcinoma, and CMTM6 positivity was associated with shorter DFS and OS [12,15]. Collectively, we consider our data are more representative to show the expression of CMTM6 in HCC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Elevated expression of CMTM6 was frequently accompanied with worse malignant phenomenon, such as with high AFP level, large tumor size, advanced TNM stage, vascular invasion in a large cohort of 619 HCC cases (In Zhu's study, only 75 HCC samples were collected). Our data was in line with other studies indicating that increased CMTM6 expression was presented in gliomaand Head and Neck Squamous Cell Carcinoma, and CMTM6 positivity was associated with shorter DFS and OS [12,15]. Collectively, we consider our data are more representative to show the expression of CMTM6 in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the depletion of CMTM6 relieves T cell immunosuppression [14]. Additionally, it has been reported that elevated CMTM6 in head and neck squamous cell carcinoma and glioma is associated with a poor prognosis [12,15], and a potential therapeutic target for renal clear cell carcinoma [16]. CMTM6 expression in combination with PD-L1 expression can be used as a prognostic and therapeutic indicator in lung cancer and pancreatic ductal adenocarcinoma [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies suggest that CMTM6 is an important factor for immune invasion by tumor cells. Further studies suggest that knocking down CMTM6 results in decreased PD-L1 expression and increased infiltration of CD8+ and CD4+ T-cells, that in turn increased the anti-tumor immunity in HNSCC 23 . CMTM6 expression is also up regulated in high grade malignant glioma and it can be correlated with poor prognosis of glioma patients 24 .…”
Section: Discussionmentioning
confidence: 96%
“…On the one hand, PD-L1, VISTA, and B7-H4 were correlated with the OSCC microenvironment, and their high expression indicates a suppressive status in OSCC ( 16 18 ). Additionally, CMTM6 is an important protein involved in the regulation of PD-L1, and CD317 is associated with B7-H4 and PD-L1 ( 36 , 37 ). On the other hand, Slug is one of the classical markers related to EMT ( 20 ).…”
Section: Discussionmentioning
confidence: 99%